COMMUNITY PERCEPTIONS ABOUT IN-VITRO MEAT OR ARTIFICIAL MEAT ON HEALTH AS A FOOD SOURCE SOLUTION FOR THE FUTURE (Lembaga Penerbitan Unversitas Esa Unggul, 2023)
In vitro meat production systems involve the raising of stem cells extracted from farm animals in the bioreactor and using modern tissue engineering techniques to produce meat outside animal feed. The question in this study is